2019
DOI: 10.1139/cjpp-2019-0055
|View full text |Cite
|
Sign up to set email alerts
|

Increase of NADPH oxidase 3 in heart failure of hereditary cardiomyopathy

Abstract: During the development of heart failure in humans and animal models, an increase in reactive oxygen species (ROS) levels was observed. However, there is no information whether this increase of ROS is associated with an increase in the density of specific isoforms of NADPH oxidases (NOXs) 1–5. The objective of this study was to verify whether the densities of NOXs 1–5 change during the development of heart failure. Using the well-known model of cardiomyopathic hamsters, the UM-X 7.1 line, a model that strongly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…NOX3 appears to have the most restricted distribution, e.g., in the inner ear, where it is essential for the formation of otoconia, calcium carbonate crystals in the vestibule responsible for the detection of linear acceleration, gravity, and audition (Paffenholz et al, 2004;Kiss et al, 2006). A recent study, however, showed NOX3 overexpression in heart failure, suggesting new physiologic roles for this isoform (Bkaily et al, 2019). Conversely, NOX4 has the most ubiquitous distribution, including in the brain, endothelium, kidney, muscle, and adipose tissue.…”
Section: Ros Generators and Toxifiers In Diseasementioning
confidence: 99%
“…NOX3 appears to have the most restricted distribution, e.g., in the inner ear, where it is essential for the formation of otoconia, calcium carbonate crystals in the vestibule responsible for the detection of linear acceleration, gravity, and audition (Paffenholz et al, 2004;Kiss et al, 2006). A recent study, however, showed NOX3 overexpression in heart failure, suggesting new physiologic roles for this isoform (Bkaily et al, 2019). Conversely, NOX4 has the most ubiquitous distribution, including in the brain, endothelium, kidney, muscle, and adipose tissue.…”
Section: Ros Generators and Toxifiers In Diseasementioning
confidence: 99%
“…The group mainly detected Nox4 mRNA expression, while Nox3 was only weakly expressed and accordingly focused on Nox4. Bkaily and colleagues further analyzed the role of Nox3 in this setting [1023]. For this purpose, they used the hereditary cardiomyopathy hamster model [1024][1025][1026], which is well established for cardiovascular disease studies [1027].…”
Section: Nox3 and Heart Failurementioning
confidence: 99%
“…It was reported that inducible NOS expression increased in failing cardiomyocytes [ 127 ]. In addition to the increase in NOS, an increase in Nox expression has also been reported during heart failure [ 128 , 129 ]. Nox is an enzyme involved in the generation of ROS [ 130 , 131 ], and ROS promotes RyR oxidation and contributes to increased channel activity ( Figure 3 B).…”
Section: Ryr Regulation Under Different Muscle Conditionsmentioning
confidence: 99%